74‐2: Collimated Flux Deposition Technology for RGB SBS OLED Displays. Issue 1 (May 2016) - Kawato, Shinichi; Inoue, Satoshi; Kobayashi, Yuhki; Mitsui, Seiichi
Abstract : We have developed a novel deposition technology that makes possible to pattern RGB SBS with high resolution onto large substrate without the mask contact. This technology is combination of evaporation flux collimation technique and scanning substrate technique above small mask, and called as Collimated Flux Deposition(CFD) Technology. Using this technology, we built 326ppi RGB Side‐by‐side display.